The prospective approach for aptamers applied in the treatment and molecular diagnostics of ischemic stroke - Li, Wenfeng; Wu, Junyi; Hu, Zijian; Zhang, Jixuan; Ye, Guangming; Luo, Fengling; Zeng, Zhikun; Luo, Yi (Frontiers in Pharmacology, 2025)
Ischemic stroke is a leading cause of death and disability worldwide. Therefore, there is a critical need to explore the underlying mechanisms and develop effective treatment strategies for ischemic stroke. As small and non-immunogenic nucleic acid molecules, aptamers can be easily chemically modified, break through the blood-brain barrier, and be screened using the classic Systematic Evolution of Ligands by Exponential Enrichment. With the advancements in emerging technologies, aptamer-based strategies have provided diagnostic and therapeutic potential for applications in central nervous system diseases. Aptamers have become a useful tool for targeted therapy and biomarker discovery in ischemic stroke. This review presents recent advances and perspectives on aptamer applications in stroke prevention, treatment, and diagnosis, focusing on targeting pathological blood clotting or thrombosis, inflammatory responses, and specific biomarkers in key cells.